Caracterização de queijo de coalho processado com culturas láticas endógenas e substituto de gordura. - Cruz, Gizele Almada (2016)
The lactic yeast and fat content of cheese contribute to its sensory characteristics. However, the consumption of food with low fat content hás been a tendency among consumers. In this regard, the use of fat substitutes hás been used as analternative to development products with low fat content and good sensory acceptance. Like wise, the use of defined lactic ferments that are made from lactic acid bactéria isolated from own cheese, is na alternative to getting safe products without promoting fundamental changes in sensory characteristics. The objective of this work was the characterization of “Coalho”cheese with fat content reduced, processed with endogenous lactic cultures (ELC) and whey protein concentrate (WPC), in order to develop a healthier alternative with equivalent sensory quality of integral cheese.For the development of this work was used factorial design 22 with different levels of WPC and ELC concentrations, with three central points, in a total of seven trials. All assays were subjected to physical, chemical and physico-chemical analysis. The means were compared by Tukey test. The effects of the independent variables on the parameters of instrumental analysis of texture (TPA) were evaluated using analysis of variance (ANOVA). The addition of WPC had a significant effect (p <0.05) on the parameters of firmness and resilience, and the ELC showed significant effect on resilience. Through the data obtained three formulations were selected by setting the concentration of ELC (2%) and varying the WPC: A (1%), B (2%) and C (3%) to sensory evaluation (testa cceptance, the ideal test and sorting-preference) and buying attitude. Microbiological analyzes were performed to verify the food safety (Salmonella, coagulase-positive staphylococci and coliforms at 45 ° C). All samples showed good acceptability. The sample A obtained the highest percentage in the evaluation for the ideal texture (51.28%), while C had the lowest percentage (10.26%). The preference ranking tests howed that samples A and B did not differ not significantly from each other (p> 0.05), both being more preferred than sample C.